2021
DOI: 10.1111/ejn.15113
|View full text |Cite
|
Sign up to set email alerts
|

More change in task repetition, less cost in task switching: Behavioral and event‐related potential evidence

Abstract: Previous studies have shown that the probability of task switching can vary the level of cognitive control and modulate the size of switch costs. However, it is unclear whether switch costs would be affected by a task‐repetition context formed by varying the degree of response (and task‐relevant stimulus property) change within the task repetition sequences while the probability of task switching remains constant. In the present study, participants were presented with a string of digits (e.g., ②②②). Basing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 105 publications
(214 reference statements)
4
7
0
Order By: Relevance
“…Consistent with this conjecture, a recent study provided evidence that when task/mental sets change more frequently, an increase in cognitive flexibility is triggered to improve task-set reconfiguration, which can lead to better task-switching performance (Zhuo et al, 2021). In MIND WANDERING AND COGNITIVE FLEXIBILITY 21 relation to this, we propose that in our study, participants with higher self-reported spontaneous mind-wandering tendencies, who also indicated higher rates of mind wandering during performance of the switching paradigms, may have triggered an increase in cognitive flexibility to a greater extent than participants with lower self-reported spontaneous mindwandering tendencies.…”
Section: Discussionmentioning
confidence: 69%
“…Consistent with this conjecture, a recent study provided evidence that when task/mental sets change more frequently, an increase in cognitive flexibility is triggered to improve task-set reconfiguration, which can lead to better task-switching performance (Zhuo et al, 2021). In MIND WANDERING AND COGNITIVE FLEXIBILITY 21 relation to this, we propose that in our study, participants with higher self-reported spontaneous mind-wandering tendencies, who also indicated higher rates of mind wandering during performance of the switching paradigms, may have triggered an increase in cognitive flexibility to a greater extent than participants with lower self-reported spontaneous mindwandering tendencies.…”
Section: Discussionmentioning
confidence: 69%
“…What requires further investigation in future studies is the role of variability in motor responses for switching-induced flexibility (see Discussion of Experiment 3). Motor variability seems to have an effect on its own, that is arguable different from the influence of frequent task switching but difficult to investigate in a confound-free manner (cf., Zhuo et al, 2021). A first hint for a dissociation of hand-specific motor preparation from nonmotor preparation processes in task switching can be found in Chen and Hsieh (2015).…”
Section: Discussionmentioning
confidence: 99%
“…5Zhuo et al (2021) investigated the influence of motor response variability in task repetition trials independently from task switch probability and found preliminary evidence from event-related potentials for altered cognitive control processes in task switch trials. While in this study the frequency of task switches was not confounded with motor response variability (because it was manipulated in task repetitions only), variability in the motor response was instead confounded with variability in task-relevant features of the target stimuli.…”
mentioning
confidence: 99%
“…It is necessary to note that the ability of deinhibition has been termed one kind of cognitive flexibility, sequential cognitive flexibility ( Wolff et al, 2018 ; Giller and Beste, 2019 ; Giller et al, 2019 ), whereas no study has been devoted to specifying the differences between deinhibition and the flexibility in switching from one task to another task. Switch cost is a typical index in measuring the cognitive flexibility in task switching ( Monsell, 2003 ; Philipp and Koch, 2005 ; Zhuo et al, 2021a , b ; Chen, 2022 ), it can be calculated by subtracting the mean reaction time (or error rate) of the repeat trials from that of the switch trials ( Allport et al, 1994 ; Monsell, 2003 ; Philipp et al, 2008 ). Most recently, Chen (2022) conducted a correlation study by comparing the RT cost in a cued switching task and the deinhibition ability in a stop-signal task.…”
Section: Discussionmentioning
confidence: 99%